Prototype of information kiosk of Shah Alam / Melissa Mohd Amran De Costa - Mohd Amran De Costa, Melissa (2004)
These days, kiosk technology has been penetrating slowly in our everyday life. Take maxis for example, they had implemented a payment through kiosk to add value for their customer services. A prototype of Information kiosk of Shah Alam has the same basic idea behind it, which is to make ease of payment and also to browse information regarding Shah Alam. Kiosk is a hardware that is located at a publicly access area. It can provide some mobility capabilities whereby user can access it while they are doing their shopping and during their leisure time. Besides that, they can also use the kiosk to pay bills during outside office hour. This research is mainly conducted in order to develop a prototype of an information kiosk of Shah Alam. The main objective of this project is to: 1) To study about information kiosk 2) To observe current kiosk system 3) To gather relevant information to build Prototype of Shah Alam Information Kiosk System 4) To develop a prototype of an information kiosk of Shah Alam. The method of doing this project is by observation and interview, other that that is the hand on which is the development of prototype. The main function in a kiosk would be interactive, relative, informative and has transaction. A kiosk may incorporate some or all the functions. The functions in the current existing kiosk had been analyzed and incorporated in PIKSA.